Guiding Principles for the Clinical Use and Selection of Microcatheters in Complex Coronary Interventions - Goel, Pravin K.; Sahu, Ankit Kumar; Kasturi, Sridhar; Roy, Sanjeeb; Shah, Nimit; Parikh, Prakashvir; Chadha, Davinder S. (Frontiers in Cardiovascular Medicine, 2022)
The use of microcatheters as a coronary interventional tool for a therapeutic approach to complex coronary interventions like bifurcation lesions, ostial location, tortuous anatomy, angled takeoffs, coronary calcification, and chronic total occlusion (CTO) percutaneous coronary intervention (PCI) is growing among cardiologists across the country. During the treatment of such complex lesions, microcatheters play an essential part of the tool kit with both single-lumen and double-lumen microcatheters (DLMs) having their specific niche areas. The selection of microcatheters involves a detailed understanding of the microcatheter specification, lesion anatomy, lesion location, vessel tortuosity and trajectory, and crossing techniques. The selection of appropriate crossing techniques with different microcatheters increases success rates of PCI, reduces procedural time and contrast use, and lowers the radiation. However, the use of microcatheters and their technicalities have not yet fully realized by many operators and their true scope has not been fully explored. This article discusses and summarizes the thoughts and key opinions of experts in this field.